Arachnandra, a new monotypic genus in Tillandsioideae (Bromeliaceae) from the Atlantic Forest in Brazil - Leme, Elton M. C.; Till, Walter; Halbritter, Heidemarie; Barfuss, Michael H. J. (Phytotaxa, 2025)
Arachnandra, a new monotypic genus of Bromeliaceae subtribe Vrieseinae, is described to accommodate a single intriguing species, Arachnandra drepanocarpa, formerly placed in either Tillandsia or Vriesea. This new genus is ecologically and morphologically distinct from the remaining genera of subfamily Tillandsioideae in its unique combination of characters including the lanceolate-acuminate sepals, petals distinctly appendaged, corolla with an open, fan blade-like shape, stamens prostrate on the corolla, pollen sulcus broad, smooth, without prominent ornamental elements, margins moderately distinct, stigma of the conduplicate-patent type, and seeds with a distinctly long basal appendaged and an inconspicuous apical one. Phylogenetic DNA sequence analyses indicate that the individuals of A. drepanocarpa form a highly supported monophyletic group in sister position to Vriesea s.str., with Vriesea and Arachnandra being sister to Stigmatodon, and all three being sister to the clade containing Alcantarea and Waltillia.